The Natural Environment of the Namib Desert - Van Damme, Patrick; Vernemmen, Patrick (Afrika Focus, 1992)
The Topnaar basically live in two distinct areas in the Namib Desert i.e. the Kuiseb river valley and the Sesfontein area. The ecology of both these zones is presented and discussed in detail. Specific attention is given to the plant communities that occur in both of them.